Safe lithium ion battery electrolyte as well as preparation method and application thereof
By introducing gas-phase silica and ammonium polyphosphate into the lithium-ion battery electrolyte, the safety and stability problems caused by the growth of negative electrode dendrites and the flammability of the electrolyte are solved, and higher circulation performance and safety are achieved.
Patent Information
- Application Number
- CN202411705805.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
AI Technical Summary
Lithium-ion batteries have low safety and stability due to the growth of negative dendrites and the flammability of the electrolyte, and the prior art is difficult to effectively solve these problems at the same time.
The gas-phase silica and ammonium polyphosphate are introduced into the lithium battery electrolyte. The two provide additional lithium ion transmission channels through synergistic effects, inhibit side reactions, improve the battery's Coulomb efficiency and capacity retention, and decompose and generate non-volatile substances during combustion to inhibit thermal runaway reactions.
It significantly improves the circulation performance, safety and stability of lithium-ion batteries, effectively suppresses the side reactions on the interface between the lithium negative electrode and the electrolyte, and reduces the occurrence of thermal runaway reactions during combustion.
Smart Images

Figure CN119518098A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a safe lithium ion battery electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and large energy storage power stations, which have significantly changed people's lifestyles and improved convenience. However, their safety issues are still prominent, especially the growth of lithium negative electrode dendrites and the flammability of electrolytes. Therefore, improving the safety of lithium-ion batteries has become an important issue that needs to be solved urgently.
[0003] In order to solve the problem of lithium dendrites, researchers have introduced a protective layer on the negative electrode or optimized the current collector design through coating or magnetron sputtering to prevent lithium dendrites from piercing the diaphragm. At the same time, in order to reduce the flammability of the electrolyte, researchers have explored complex polymer synthesis pathways and developed non-flammable flame retardant additives to improve electrolyte performance. Although these measures have shown certain effects in theory and experiments, they usually involve complex preparation processes and cannot effectively solve the problems of lithium dendrite growth and electrolyte flammability at the same time.
[0004] Therefore, it is urgent to improve the safety and stability of lithium-ion batteries through simple and efficient material innovation and optimized design, so as to promote their reliable application in various fields and promote the sustainable development of energy. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a safe lithium-ion battery electrolyte and its preparation method and application, aiming to solve the technical problems of low safety and stability of lithium-ion batteries caused by the growth of negative electrode dendrites and the flammability of the electrolyte.
[0006] In a first aspect, the embodiments of the present application provide a safe lithium-ion battery electrolyte and a preparation method and application thereof, which, by weight, comprises 70 to 94 parts of a non-aqueous organic solvent, 5 to 20 parts of a lithium salt, 0.4 to 8 parts of ammonium polyphosphate, 0.1 to 1 parts of fumed silica and 0.5 to 1 parts of a dispersant.
[0007] In the technical solution of the embodiment of the present application, fumed silica and ammonium polyphosphate are introduced into the lithium battery electrolyte. The synergistic effect of the two not only effectively improves the cycle performance of the lithium-ion battery, but also effectively improves the safety of the battery.
[0008] The surface of fumed silica particles contains -OH groups, which can spontaneously adsorb Li +, accelerate the lithium ion transmission near the electrode / electrolyte interface, provide additional transmission paths for lithium ions, make lithium deposition more uniform, and inhibit side reactions at the interface between the lithium negative electrode and the electrolyte, thereby improving the coulombic efficiency of the battery. The phosphate groups on ammonium polyphosphate can form coordination with lithium ions, promote lithium ion migration, accelerate its desolvation process, improve lithium ion deposition kinetics, and improve the battery's capacity retention rate.
[0009] In addition, fumed silica and ammonium polyphosphate provide additional lithium ion transmission channels through coordination, guide lithium ions to deposit evenly, inhibit the occurrence of side reactions, and further improve the coulombic efficiency and capacity retention rate of the battery. When the battery burns, ammonium polyphosphate can quickly decompose to form non-volatile phosphorus oxides and polyphosphoric acid, and fumed silica forms silicon-based substances. These substances can cover the surface of the electrode to form a barrier, reduce the contact between the active material and the electrolyte, and effectively inhibit the thermal runaway reaction inside the battery.
[0010] Preferably, the non-aqueous organic solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1-4-butyrolactone, carboxylic acid esters, and sulfite esters.
[0011] Preferably, the lithium salt is one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluorophosphate, lithium perchlorate, lithium trifluoromethanesulfonate, and lithium bis(oxalatoborate).
[0012] Preferably, the dispersant is one or more of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate, and sodium lauryl sulfate.
[0013] In a second aspect, the present application provides a method for preparing a safe lithium-ion battery electrolyte, comprising the following steps: S1. Add lithium salt to a non-aqueous organic solvent and stir to uniformly disperse the lithium salt to obtain a mixed solution; S2. After drying the fumed silica, add it, a dispersant and ammonium polyphosphate into the mixed solution of step S1, and obtain a lithium ion battery electrolyte after stirring and ultrasonic dispersion.
[0014] Preferably, the stirring time in step S1 is 5 to 60 minutes.
[0015] Preferably, in step S2, the stirring temperature is 20-80° C., the stirring time is 10-120 min, and the stirring speed is 200-1000 rpm.
[0016] Preferably, the ultrasonic treatment time is 10 to 120 min.
[0017] In a third aspect, an embodiment of the present application provides a safe lithium-ion battery, including a lithium-ion battery electrolyte.
[0018] Different from the existing technical solutions, the beneficial effects of this application include: 1. This application introduces fumed silica and ammonium polyphosphate into the lithium battery electrolyte. The synergistic effect of the two not only effectively improves the cycle performance of the lithium-ion battery, but also effectively improves the safety of the battery. Fumed silica particles can inhibit side reactions at the interface between the lithium negative electrode and the electrolyte, thereby improving the coulombic efficiency of the battery. Fumed silica and ammonium polyphosphate synergistically provide additional lithium ion transmission channels through coordination, guide the uniform deposition of lithium ions, inhibit the occurrence of side reactions, and further improve the coulombic efficiency and capacity retention rate of the battery.
[0019] 2. When the battery burns, ammonium polyphosphate can quickly decompose to produce non-volatile phosphorus oxides and polyphosphoric acid, and fumed silica forms silicon-based substances. These substances can cover the surface of the electrode to form a barrier, reducing the contact between the active substance and the electrolyte, thereby effectively inhibiting the thermal runaway reaction inside the battery.
[0020] 3. The electrolyte developed in this application can not only significantly improve the safety of the battery, but also effectively improve the coulombic efficiency and capacity retention rate of the battery, showing good application prospects.
[0021] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 This is a test chart of the capacity retention rate of a lithium-ion battery prepared using the electrolyte prepared in Example 1.
[0024] Figure 2 This is a test chart of the capacity retention rate of a lithium-ion battery prepared using the electrolyte prepared in Comparative Example 1.
[0025] Figure 3 This is a test chart of the capacity retention rate of a lithium-ion battery prepared using the electrolyte prepared in Comparative Example 2.
[0026] Figure 4 This is a test chart of the capacity retention rate of a lithium-ion battery prepared using the electrolyte prepared in Comparative Example 3.
[0027] Figure 5 This is a test chart of the capacity retention rate of a lithium-ion battery prepared using the electrolyte prepared in Comparative Example 4. DETAILED DESCRIPTION
[0028] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0030] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0031] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0032] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0033] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0034] In order to solve the problem of lithium dendrites, researchers have introduced a protective layer on the negative electrode or optimized the current collector design through coating or magnetron sputtering to prevent lithium dendrites from piercing the diaphragm. At the same time, in order to reduce the flammability of the electrolyte, researchers have explored complex polymer synthesis pathways and developed non-flammable flame retardant additives to improve electrolyte performance. Although these measures have shown certain effects in theory and experiments, they usually involve complex preparation processes and cannot effectively solve the problems of lithium dendrite growth and electrolyte flammability at the same time.
[0035] In order to solve the technical problem that the safety and stability of lithium-ion batteries are not high due to the growth of negative electrode dendrites and the flammability of the electrolyte, the present application provides a safe lithium-ion battery electrolyte and its preparation method and application, wherein the present application introduces fumed silica and ammonium polyphosphate into the lithium battery electrolyte, and the synergistic effect of the two not only effectively improves the cycle performance of the lithium-ion battery, but also effectively improves the safety of the battery. Fumed silica particles can inhibit side reactions at the interface between the lithium negative electrode and the electrolyte, thereby improving the coulombic efficiency of the battery. Fumed silica and ammonium polyphosphate synergistically provide additional lithium ion transmission channels through coordination, guide the uniform deposition of lithium ions, inhibit the occurrence of side reactions, and further improve the coulombic efficiency and capacity retention rate of the battery.
[0036] In a first aspect, the embodiments of the present application provide a safe lithium-ion battery electrolyte and a preparation method and application thereof, which, by weight, comprises 70 to 94 parts of a non-aqueous organic solvent, 5 to 20 parts of a lithium salt, 0.4 to 8 parts of ammonium polyphosphate, 0.1 to 1 parts of fumed silica and 0.5 to 1 parts of a dispersant.
[0037] In the technical solution of the embodiment of the present application, fumed silica and ammonium polyphosphate are introduced into the lithium battery electrolyte. The synergistic effect of the two not only effectively improves the cycle performance of the lithium-ion battery, but also effectively improves the safety of the battery.
[0038] The surface of fumed silica particles contains -OH groups, which can spontaneously adsorb Li + , accelerate the lithium ion transport near the electrode / electrolyte interface, provide additional transport paths for lithium ions, make lithium deposition more uniform, and inhibit side reactions at the interface between the lithium negative electrode and the electrolyte, thereby improving the coulombic efficiency of the battery.
[0039] The phosphate groups on ammonium polyphosphate can form coordination with lithium ions, promote lithium ion migration, accelerate its desolvation process, improve lithium ion deposition kinetics, and enhance the battery's capacity retention rate. Conventional macromolecular phosphorus-containing flame retardants, such as DOPO-containing polymer flame retardants and bispirocyclic polyphosphate flame retardants, are difficult to dissolve in the electrolyte. Although small molecule phosphorus-containing flame retardants can be dissolved in the electrolyte, they will have side reactions at the negative electrode. The chemical properties of ammonium polyphosphate are relatively stable, making it suitable as a flame retardant for lithium-ion battery electrolytes.
[0040] In addition, fumed silica and ammonium polyphosphate provide additional lithium ion transmission channels through coordination, guide lithium ions to deposit evenly, inhibit the occurrence of side reactions, and further improve the coulombic efficiency and capacity retention rate of the battery. When the battery burns, ammonium polyphosphate can quickly decompose to form non-volatile phosphorus oxides and polyphosphoric acid, and fumed silica forms silicon-based substances. These substances can cover the surface of the electrode to form a barrier, reduce the contact between the active material and the electrolyte, and effectively inhibit the thermal runaway reaction inside the battery.
[0041] Preferably, the non-aqueous organic solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1-4-butyrolactone, carboxylic acid esters, and sulfite esters.
[0042] Preferably, the lithium salt is one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluorophosphate, lithium perchlorate, lithium trifluoromethanesulfonate, and lithium bis(oxalatoborate).
[0043] Preferably, the dispersant is one or more of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate, and sodium lauryl sulfate.
[0044] In a second aspect, the present application provides a method for preparing a safe lithium-ion battery electrolyte, comprising the following steps: S1. Add lithium salt to a non-aqueous organic solvent and stir to uniformly disperse the lithium salt to obtain a mixed solution; S2. After drying the fumed silica, add it, a dispersant and ammonium polyphosphate into the mixed solution of step S1, and obtain a lithium ion battery electrolyte after stirring and ultrasonic dispersion.
[0045] Preferably, the stirring time in step S1 is 5 to 60 minutes.
[0046] Preferably, in step S2, the stirring temperature is 20-80° C., the stirring time is 10-120 min, and the stirring speed is 200-1000 rpm.
[0047] Preferably, the ultrasonic treatment time is 10 to 120 min.
[0048] In a third aspect, an embodiment of the present application provides a safe lithium-ion battery, including a lithium-ion battery electrolyte.
[0049] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0050] 1. Preparation method Example 1 (1) Lithium hexafluorophosphate was added to a mixed solvent of ethylene carbonate and dimethyl carbonate (the non-aqueous organic solvent accounted for 85 wt% of the total mass of the electrolyte, and the volume ratio of ethylene carbonate to dimethyl carbonate was 1:1) at a concentration of 10 wt% relative to the total mass of the electrolyte, and magnetic stirring was performed for 20 min; (2) 0.5 wt% of fumed silica, 0.5 wt% of polyvinyl pyrrolidone, and 4 wt% of ammonium polyphosphate were added to the solution in (1), stirred at room temperature for 4 h to dissolve, and subjected to ultrasonic dispersion for 2 h to obtain the lithium ion battery electrolyte.
[0051] Example 2 Other conditions are the same as those in Example 1, except that the proportions of the non-aqueous organic solvent and lithium hexafluorophosphate in the electrolyte are 80 wt % and 15 wt %, respectively.
[0052] Example 3 Other conditions are the same as those in Example 1, except that the proportions of the non-aqueous organic solvent and lithium hexafluorophosphate in the electrolyte are 90 wt % and 5 wt %, respectively.
[0053] Example 4 The other conditions are the same as those in Example 1, except that in step (2), the proportions of fumed silica, polyvinyl pyrrolidone, and ammonium polyphosphate in the electrolyte are 1 wt%, 1 wt%, and 3 wt%, respectively.
[0054] Example 5 The other conditions are the same as those in Example 1, except that in step (2), the proportions of fumed silica, polyvinyl pyrrolidone, and ammonium polyphosphate in the electrolyte are 0.8 wt%, 0.8 wt%, and 3.4 wt%, respectively.
[0055] Example 6 The other conditions are the same as those in Example 1, except that in step (2), the proportions of fumed silica, polyvinyl pyrrolidone, and ammonium polyphosphate in the electrolyte are 0.1 wt%, 0.1 wt%, and 4.8 wt%, respectively.
[0056] Example 7 The other conditions are the same as those in Example 1, except that the lithium salt in step (1) is lithium tetrafluoroborate.
[0057] Example 8 The other conditions were the same as those in Example 1, except that the non-aqueous organic solvent in step (1) was a mixed solvent of diethyl carbonate and ethyl methyl carbonate (the volume ratio of diethyl carbonate to ethyl methyl carbonate was 1:1).
[0058] Example 9 The other conditions are the same as those in Example 1, except that the dispersant in step (2) is sodium dodecylbenzene sulfonate.
[0059] Comparative Example 1 The other conditions are the same as those in Example 1, except that the proportions of the non-aqueous organic solvent and the lithium salt in the electrolyte are 90 wt % and 10 wt %.
[0060] Comparative Example 2 Other conditions are the same as those in Example 1, except that the proportions of the non-aqueous organic solvent, lithium salt, polyvinyl pyrrolidone, and ammonium polyphosphate in the electrolyte are 85.5 wt%, 10 wt%, 0.5 wt%, and 4 wt%, respectively.
[0061] Comparative Example 3 The other conditions are the same as those in Example 1, except that the proportions of the non-aqueous organic solvent, lithium salt, and fumed silica in the electrolyte are 89.5 wt%, 10 wt%, and 0.5 wt%, respectively.
[0062] Comparative Example 4 The other conditions are the same as those in Example 1, except that the flame retardant in step (2) is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO).
[0063] 2. Test Method The above lithium-ion battery electrolyte is matched with a lithium iron phosphate positive electrode, a lithium metal negative electrode and a polypropylene separator to assemble a lithium-ion battery. The relevant steps are as follows: (1) Preparation of lithium iron phosphate positive electrode sheet: The positive electrode active material lithium iron phosphate (180 mg), conductive carbon (10 mg), and polyvinylidene fluoride (10 mg) were mixed in a mass ratio of 9:0.5:0.5, and 0.7 mL of N-methyl-2-pyrrolidone was added. The mixture was ground for 30 min to make a slurry and coated on the aluminum current collector. The slurry was then dried in a blast oven at 60 °C for 2 h, and then dried in a vacuum oven at 80 °C for 12 h. Finally, the slicing was performed to obtain a circular positive electrode sheet with a diameter of 12 mm.
[0064] (2) Assembly of lithium-ion batteries: The batteries involved in the present invention are all button-type batteries, and the batteries are assembled in an argon atmosphere glove box with an oxygen content of 0.01 ppm and a water content of 0.01 ppm. The specific operation process is as follows: Place the positive electrode sheet with the side coated with the active material facing up in the positive electrode shell, cover the lithium iron phosphate positive electrode sheet with a polypropylene diaphragm with a diameter of 16 mm, and then drip 50 uL of electrolyte. Put the lithium sheet, stainless steel gasket and stainless steel spring in turn, and finally buckle the negative electrode shell. Use a sealing machine to seal the battery, and let the battery stand for 12 hours to ensure sufficient infiltration of the electrolyte. Subsequently, the charge and discharge cycle test was carried out at a rate of 0.2 C in the blue battery test system. The results are shown in Table 1.
[0065] III. Analysis of test results of various embodiments and comparative examples (1) The lithium ion batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 4 were subjected to electrochemical tests. The results are shown in Table 1.
[0066] Table 1 Electrochemical test data of lithium ion batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 4
[0067] According to the data of Example 1 and Comparative Example 1 in Table 1, it can be seen that the lithium ion battery electrolyte provided by the present invention can significantly improve various cycle performances of the battery, such as the capacity retention rate and the average coulomb efficiency.
[0068] According to Table 1 and Figures 1 to 4 It can be seen that although both fumed silica and ammonium polyphosphate improve the battery's cycle performance individually, the synergistic improvement is the most obvious. This is because fumed silica and ammonium polyphosphate provide additional lithium ion transmission channels through coordination, guide lithium ions to deposit evenly, inhibit the occurrence of side reactions, and further improve the battery's coulombic efficiency and capacity retention rate.
[0069] Comparative Example 4 replaces the flame retardant component relative to Example 1. Figure 1 , Figure 5It can be seen from the data that when the flame retardant component in the battery system is replaced with other types, the performance of the battery is significantly reduced. This phenomenon clearly indicates that the change of flame retardant components has an adverse effect on battery performance.
[0070] According to the test data of Examples 1 to 3 in Table 1, it can be found that although the electrolytes composed of non-aqueous organic solvents and lithium salts in different proportions have improved the cycle performance of the battery, the degree of improvement in performance is different. Among them, when the mass fractions of non-aqueous organic solvents and lithium salts in the electrolyte are 85 wt% and 10 wt%, respectively, the cycle performance of the battery is improved most significantly. According to Examples 1 and 4 to 6, it was found that different amounts of added fumed silica, polyvinyl pyrrolidone, and ammonium polyphosphate have different degrees of improvement in the performance of lithium-ion batteries. Among them, when the mass fractions of fumed silica, polyvinyl pyrrolidone, and ammonium polyphosphate in the electrolyte are 0.5 wt%, 0.5 wt%, and 4 wt%, respectively, the cycle performance of the battery is improved the most. According to Examples 7 to 9, it was found that changing the types of lithium salts, anhydrous organic solvents, and dispersants had no significant effect on battery performance.
[0071] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and playing the same role within the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A safe lithium-ion battery electrolyte, characterized in that: Calculated by weight, it includes 70-94 parts of non-aqueous organic solvent, 5-20 parts of lithium salt, 0.4-8 parts of ammonium polyphosphate, 0.1-1 parts of fumed silica and 0.5-1 parts of dispersant.
2. The safe lithium-ion battery electrolyte according to claim 1, characterized in that: The non-aqueous organic solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1-4-butyrolactone, carboxylic acid esters, and sulfite esters.
3. The safe lithium-ion battery electrolyte according to claim 1, characterized in that: The lithium salt is one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluorophosphate, lithium perchlorate, lithium trifluoromethanesulfonate, and lithium bis(oxalatoborate).
4. The safe lithium-ion battery electrolyte according to claim 1, characterized in that: The dispersant is one or more of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate, and sodium lauryl sulfate.
5. A method for preparing a safe lithium-ion battery electrolyte according to any one of claims 1 to 4, characterized in that: The steps include: S1. Add lithium salt to a non-aqueous organic solvent and stir to uniformly disperse the lithium salt to obtain a mixed solution; S2. After drying the fumed silica, add it, a dispersant and ammonium polyphosphate into the mixed solution of step S1, and obtain a lithium ion battery electrolyte after stirring and ultrasonic dispersion.
6. The method for preparing a safe lithium-ion battery electrolyte according to claim 5, characterized in that: The stirring time in step S1 is 5 to 60 minutes.
7. The method for preparing a safe lithium-ion battery electrolyte according to claim 5, characterized in that: In step S2, the drying temperature of the fumed silica is 60-100° C., and the drying time is 12-36 hours.
8. The method for preparing a safe lithium-ion battery electrolyte according to claim 5, characterized in that: In step S2, the stirring temperature is 20-80° C., the stirring time is 10-120 min, and the stirring speed is 200-1000 rpm.
9. The method for preparing a safe lithium-ion battery electrolyte according to claim 5, characterized in that: The ultrasonic treatment time is 10 to 120 minutes.
10. A safe lithium-ion battery, characterized in that: A lithium ion battery electrolyte comprising the electrolyte of any one of claims 1 to 4.
Citation Information
Patent Citations
Electrolyte for inhibiting lithium dendrites and preparation method thereof, and lithium battery
CN107275671A
Flame-retardant electrolyte for lithium ion battery
CN107799814A